A perspective on fat intake in athletes - Pendergast, D. R.; Leddy, J. J.; Venkatraman, J. T. (Journal of the American College of Nutrition, 2000)
Performance in endurance events is dependent upon the maximal aerobic power, the percentage of that power that can be sustained and the availability of substrates (carbohydrates [CHO] and fats). The purpose of this paper is to present a perspective of recent studies that demonstrate the role of fat intake and oxidation on endurance performance. Studies have shown that fatigue is associated with reduced muscle glycogen and that increasing muscle glycogen or blood glucose prolongs performance while increasing fat and decreasing CHO decreases performance. This has led to an emphasis on CHO intake in athletes in endurance sports, which quite often leads to low caloric intake. It is well known that trained subjects have higher levels of fat oxidative capacity, which spares glycogen during endurance sports. Data from recent studies in trained athletes, who were fed iso-caloric high-fat diets (42% to 55%) that maintained adequate CHO levels, have shown an increase in endurance in both men and women when compared to diets composed of low fat intake (10% to 15%). The magnitude of the effect on endurance was significant at high percentages of maximal aerobic power and increased as the percentage of maximal aerobic power decreased. Based on this review, a baseline diet comprising 20% protein, 30% CHO and 30% fat, with the remaining 20% of the calories distributed between CHO and fat based on the intensity and duration of the sport, is recommended for discussion and future research.